The Existence of Librarians in the Digital Era in College Libraries in Mataram City - Iskandar, Iskandar; Hapsari, Nurul Fikriati Ayu; Susilawati, Hirma (Tibanndaru : Jurnal Ilmu Perpustakaan dan Informasi, 2026)
Purpose Research. To identify the existence of librarians in the digital era seen from the fulfillment of librarians' needs in carrying out their functions as library managers. Research Method. Using a qualitative descriptive approach conducted in 4 state and private university libraries in Mataram City. The selection of informants was carried out by purposive sampling. Analysis Data. While the stages of data analysis are data reduction, data presentation, and data verification. Results. The results of this study indicate that physiological needs, security needs, comfort needs, appreciation needs, and self-actualization needs are important needs for librarians in achieving well-being and improving competence, so that librarians continue to exist in the current digital era. However, various obstacles faced by librarians continue to exist in the current digital era, one of which is being responsive to information technology. Conclusions. The performance of librarians can be improved by looking at the fulfillment of the needs that have been obtained by librarians, so that the existence of librarians in the digital era can be achieved. Keywords: Existence of Librarians, College Libraries, Fulfillment of Needs